Effectiveness Of The Implementation Of The Policy On The Use Of The Ciledug Road Sidewalk In Garut Regency As Urban Space - Firdaus, Syakira (Universitas Negeri Semarang, 2026)
Urban development is fundamentally linked to the issue of space. As the population grows and community activities increase, the need for space also increases. As a result, urban spaces become increasingly crowded as they accommodate various human activities, including sidewalks. On CiledugStreet in Garut Regency, sidewalks that are supposed to be used by pedestrians are also used for economic activities and other purposes. This study aims to analyze the effectiveness of the implementation of sidewalk use policies and identify the factors that influence them, through qualitative research methods with empirical legal analysis, using a legislative approach and a case approach that aims to understand how the law works in the practice of urban space utilization, particularly in relation to the use of sidewalks on Ciledug Road in Garut Regency. The data in this study were obtained through primary and secondary data. Primary data were collected through in-depth interviews with the Garut Regency Civil Service Police Unit as the authority in charge of supervising and regulating space utilization, as well as with the Ciledug Road users who are directly affected by sidewalk use. The results of the study show that policy implementation has not been effective due to inconsistent supervision, limited coordination, and the economic needs of the community that influence the use of space. This study contributes to broadening the understanding that the effectiveness of urban space policies is not only measured by compliance with regulations, but also by the ability of these policies to adapt to social realities.